Variation of Karonese Language in Tanah Karo - Tarigan, Jenheri Rejeki; Aisyah Ginting, Siti; Husein, Rahmad (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 23 No 1 (2023)DO - 10.24843/PJIIB.2023.v23.i01.p06, 2023)
This study aims to know the Variation of Karonese Language in Tanah Karo. This study was conducted by using descriptive qualitative research. This study were done at some places in Tanah Karo. There were at Tigapanah, Tiganderket and Tigabinanga. There were 6 people taken as subject (informant)  in this study. The data was collected by giving Swadesh (Phoneme and Lexical) and also by interviewed the native speaker of Karonese. The result of the study dominantly same, but there are some words are different in Phoneme based on three palces in Tanah Karo, such us: they say satu, in Tigapanah /sada/, Tiganderket /sada/ and Tigabinanga /sadæ/ and also result of the lexical are also domintaly same but there are some words are different such us; in Tigapanah people say “benar” they say  “tuhu”, in Tiganderket people say “benar” they say “ tuhu” and in Tigabinanga people say “benar” they say “payo”. So, based on the swadesh (Phoneme and Lexical) and interview, this study accumulate to increase the understanding of variation of Karonese language and for present to the readers about variation of Karonese language and it caused by (1) Regional Dialect and (2) Arena or Geography.